Mitigation, Adaptation and Coping Strategies of Forest and Farming Dependent Communities from Impacts of Global Climate Change - Chakravarty, Sumit; Dey, Tanusri; Pala, Nazir A.; Shukla, Gopal (Indian Forester, 2019)
The forest dwellers, adjacent farmers and even considerable proportion of underprivileged population are particularly at risk due to climate change. This climate change is projected to adversely impact rural livelihoods especially forest communities dependent on climate sensitive natural resources. There is a dearth of literature that describes the challenges and solutions of climate change. Literature describing the roles of institutions in mitigating and adapting to climate change is also scanty. Work on climate mitigation and adaptation needs to be carried out in specific region to better understand which policies are most likely to resonate with public support and which might be most difficult to implement. Therefore, an attempt has been made in this review article to identify various factors that influence adaptation strategies pursued by the forest dependent and other farming communities’ in response to climate variability and change. Studies have identified different factors viz., socio-economic, cultural, political, geographical, knowledge and information support, technology adoption, public action, age and gender and institutional adopted by the communities in response to the risk associated with climatic variability. The present work has in response also identified various coping strategies like agroforestry, farm operations, local traditional measures, crop diversification, local knowledge and change in life style to combat the adverse effects of climate change.